Time-updated patterns of hemoglobin and hematocrit and the risk of CKD progression - Fu, Li-zhe; Chen, Hui-fen; Shen, Yu-han; Zhang, Xian-long; Tang, Fang; Hu, Xiao-xuan; Liu, Zhen-jie; Ouyang, Wen-wei; Liu, Xu-sheng; Wu, Yi-fan (Frontiers in Endocrinology, 2025)
BackgroundEarly intervention and management of anemia, particularly the commonly used measures of hemoglobin (Hb) and hematocrit (HCT), are important in slowing and preventing the progression of chronic kidney disease (CKD). However, the optimal range for regulating Hb and HCT levels remains uncertain.ObjectiveThe aim of this study was to elucidate the intrinsic relationship between Hb and HCT and the short- and long-term prognosis of CKD, and determine optimal ranges for Hb and HCT.MethodsWe retrospectively collected demographic and clinical data over a 6-year follow-up period in Lingnan, China, to show the long-term characteristics of Hb and HCT, and studied the association between Hb, HCT, and the prognosis of patients with CKD stages 3–4. We constructed Cox and group-based trajectory modeling (GBTM) models to examine Hb’s and HCT’s associations with short- and long-term risk of composite outcomes in patients with CKD stages 3–4.ResultsA total of 730 individuals were included, with a median age of 59.30 (48.47, 68.63) years, 306 (41.92%) were women, and median eGFR was 39.24 (26.26, 50.67) mL/min/1.73 m2. A multivariate time-dependent Cox model revealed mean_Hb and mean_HCT as independent protective factors for the composite outcome {hazard ratio (HR) (95% confidence interval [CI]): 0.851 (0.786, 0.921) g/L, p=0.000; 0.578% (0.441%, 0.758%), p=0.000}. Optimized GBTM models categorized Hb and HCT into four groups. Group 1 (“lower and decreasing”) (Hb<100 g/L, HCT approximately 30%) served as the reference. Groups 2 (“lower and growing slightly”) (Hb 110–120 g/L, HCT approximately 35%), 3 (“higher and growing slightly”) (Hb 125–135 g/L, HCT approximately 40%), and 4 (“higher and growing steadily”) (Hb 145–160 g/L, HCT approximately 45%) served as independent protective factors for patients with CKD stages 3–4 for the composite outcome (p=0.000; p for trend<0.000). Subgroup analyses showed interactions between mean_Hb and sex (p for interaction=0.034), as well as between Hb trajectory group 2 and CKD stage (p for interaction=0.015).ConclusionsMaintenance of stable and higher Hb levels of 110–130 g/L and HCT levels of 35%–40% in patients with CKD stages 3–4 is both protective and reliable in delaying CKD progression.